PENGARUH PEMASARAN RELASIONAL DAN HARGA TERHADAP KEPUASAN DAN LOYALITAS PELANGGAN TOKOPEDIA PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS RIAU TAHUN AKADEMIK 2017-2018 - Johar, M Fikhri; Alwie, Alvi Furwanti; Jahrizal, Jahrizal (Jurnal Tepak Manajemen Bisnis, 2018)
Along with the development of e-commerce industry in Indonesia, it hasmany emerging various vendors (sites) service providers online shopping. In theface of e-commerce industry in Indonesia, Tokopedia has a major competitor,Kaskus, and other competitors such as Bukalapak, OLX, Berniaga, Lamido,Rumah, Sribu, Elevenia, other e-commerce sites. The large number of ecommercesite providers, has created competition and ease of access forconsumers, as well as ease to move using e-commerce services. To face thecompetition, the company must be able to understand about the factors thatinfluence consumer loyalty. Among which will be investigated is the problem ofrelational marketing, price and customer satisfaction.The purpose of this study is to analyze the influence of relational marketing andprice to customer satisfaction and loyalty of Tokopedia in Economic and BusinessFaculty University Of Riau Academic 2017-2018 Students. This study wasconducted on the students of Riau University with the sample used is as many as170 respondents who use Tokopedia. Techniques data collection used is aquestionnaire with Likert scale. SEM analysis becomes hypothesis test tool usingsmartPls 3.00 and SPSS 17.00 for Windows program.Results of the research, it can be concluded: 1) relational marketing and priceinfluence on satisfaction; 2) relational marketing and price affects consumerloyalty; 3) satisfaction affects consumer loyalty. Therefore, to create customersatisfaction and loyalty, the company can improve the brands relationalmarketing, providing various price variations and payment methods.